Drug resistant pathogens, their resistance genes, and cost implications - Thapa, B (International Journal of Infection and Microbiology, 2013)
DOI: http://doi.dx.org/10.3126/ijim.v2i1.8001 Int J Infect Microbiol 2013;2(1):1-2